Drivers and impacts in the globalization of corporate R&D: An introduction based on the European experience - Pietro Moncada-Paternò-Castello; Marco Vivarelli; Peter Voigt (Institute for the Study of Labor (IZA), 2011)
The globalization of R&D activities has continued its growth path as companies are increasingly trying to capture knowledge and market opportunities internationally. The rapid evolution of national economies and the ways to conduct knowledge-intensive businesses has led researchers and analysts to pursue a deeper understanding of the globalization of corporate R&D and the related driving factors and impacts. This introduction to the Special Section: Globalization and Corporate R&D forthcoming in Industrial and Corporate Change (vol. 20 (2), April 2011) provides an update of trends in the globalization of corporate R&D. It reviews the literature on the main drivers and impacts of the process under investigation, introduces the papers for this Special Section, and offers some concluding remarks.
urn:nbn:de:101:1-201104134047
Keywords: F23; O32; 330; globalization; R&D; outsourcing; FDI; Forschung; Industrielle Forschung; Globalisierung; Multinationales Unternehmen; Standortwahl; Industriestaaten